NPA: A COMPARATIVE STUDY OF PNB AND HDFC BANK (International Journal of Food and Nutritional Sciences, 2022)
Bank is always considered as back bone of the financial system of any economy. Financial inclusion is the main need of an economy. Banks and others financial institutions play the vital role in financial inclusion of an economy of country. Today’s globalised economies; banks are safe source of finance to individual and corporations. The knowledge of financial performance helps decision makers to predict, comp are and evaluate the earning ability of banks and companies. This research study is descriptive and analytical in nature. The data used for this research paper is entirely secondary in nature. In this study, Gross and Net NPA of PNB and HDFC Bank is evaluated and compared. The study shows the NPA of PNB and HDFC. The study shows that the NPA position of HDFC Bank is better than PNB.